Towards altering canonical status: A case for Catholic universities and colleges in Canada. - Zorzi, Daniel J. (University of Ottawa (Canada), 1995)
In the Apostolic Constitution, Ex corde Ecclesiae, John Paul II states that the Catholic university and college is a human institution wherein the members critically assist in the on-going promotion of human dignity and cultural heritage through the three-fold missions of teaching, researching, and providing various pastoral services. Moreover, the members perform these tasks, imbued with the Christian spirit and inspired with the Gospel values in order to "assure in an institutional manner a Christian presence in the university world confronting the great problems of society and culture." In short, the institution marks the confluence of two streams within a Catholic academic environment--culture and religion. Church legislation has remained neither silent nor irrelevant on the question of Catholic higher education. In fact, the 1983 Code of Canon Law devotes several canons of related issues pertinent to these institutions. It does not, however, systematically address the critical topic of church-related educational institutions with respect to religiously-owned universities and colleges and their canonical status. Instead, in a more general way, the 1983 Code introduces new and broader options for canonical status, including the public and private juridic person and the public and private associations of the faithful with or without juridic personality. Consequently, at the heart of this dissertation lies the issue of canonical status of religiously-owned federated Catholic universities and colleges in Canada; the crux of the matter is the precise determination of and alteration to that canonical status, given the broader designations in the 1983 Code. Accordingly, based on the presumption that tracing the titles to property of religiously-owned educational institutions is the truest indicator of its present canonical status, this dissertation undertakes a canonical investigation into the titles to property of the Basilian-owned, Canadian federated Assumption University at Windsor, Ontario. Selecting and properly applying an option, if appropriate, presents innovative ways to direct various educational institutions within particular settings and under different governance models, while ensuring, among other concerns, the protection against exposure to civil and canonical liabilities of church-related institutions and the on-going mission of the Catholic university.
Keywords: Religion, General.